Experiences of Thabazimbi Resident Mine Employees Regarding the Perceived Effects of Mining Activities within their Community. The case of Amandelbult Mine in Limpopo, South Africa - Ditshego, Mashiatshiti Johanna (University of the Witwatersrand, Johannesburg, 2023)
South Africa’s mining industry has historically been at the heart of the nation’s economy also taking into consideration the country’s high-ranking spot as one of the leading naturally rich resource countries within the world. In reality, the mining industry has played a key part in contributing to the country’s economic growth, and it remains South Africa’s most watched financial segment. However, the mining industry has experienced a major turmoil, since it also brings along socially unintended circumstances within the communities that they operate in, for example an increase of informal settlement, spontaneous mine closures, and the perpetuation of fights inside traditional houses. As much as there are several studies done within the South African mining sector, studies looking into the experiences and perceived effects of mining activities in communities where these mining companies operate are very limited within the South African literature in Occupational Social Work. Therefore, this qualitative study sought to close this gap, as it aims to explore the experiences of Thabazimbi Resident Mine Employees Regarding the Perceived Effects of Mining Activities within their Community. The study was qualitative in nature, with a case study used as the research design. The target population was mine employees residing in Thabazimbi. Purposive sampling was used to recruit (10) mine employees and (2) key informants in the community to be participants for the study, with a semi-structured interview guide employed as a research instrument. Data for the study was collected using face-to-face individual interviews. Thematic analysis was used to analyse the findings. Findings indicate that mining activities had both positive and negative experiences for the resident employees. Thabazimbi resident employees suggested some recommendations that can be implemented to mitigate the negative effects that they raised in the findings. Recommendations are made in relation future research.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Social Work (Occupational Social Work) to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: Experiences; Mining; Mining Activities; Social Labour Plans; Limpopo Province - South Africa; UCTD; SDG-8: Decent work and economic growth